Solutions to technical challenges during therapeutic plasma exchange using the Spectra Optia on a 4 kilogram neonate. Issue 2 (April 2018) - Mathur, Gagan; Collins, Laura; Tigges, Cody R.; Schlueter, Annette J.
Abstract: Therapeutic plasma exchange (TPE) on severely ill neonates poses many technical challenges, including obtaining adequate vascular access. In addition, clinical challenges such as risk of hypotension and cardiovascular instability are more pronounced in these patients. We report an approach to successfully managing these challenges while performing TPE on a 4 kilogram neonate using the Spectra Optia and 22 G venous access.